2021
DOI: 10.1101/2021.03.01.433450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous neural oscillations influence behavior and sensory representations by suppressing neuronal excitability

Abstract: The ability to process and respond to external input is critical for adaptive behavior. Why, then, do neural and behavioral responses vary across repeated presentations of the same sensory input? Spontaneous fluctuations of neuronal excitability are currently hypothesized to underlie the trial-by-trial variability in sensory processing. To test this, we capitalized on invasive electrophysiology in neurosurgical patients performing an auditory discrimination task with visual cues: specifically, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 142 publications
(229 reference statements)
2
7
0
Order By: Relevance
“…Consistent with the predictions, the presence of non-zero OM has been previously directly confirmed (Nikulin et al, 2007, Nikulin et al, 2010) and the generation of evoked responses has been found to be consistent with the idea of BSM (Mazaheri and Jensen, 2008, Iemi et al, 2019, Iemi et al, 2021). Moreover, many empirical studies assessed cognitive functioning with simultaneous analysis of evoked responses and oscillations, with the results showing consistent correlation of evoked response amplitude and/or latency with the modulation in oscillations (Yordanova et al, 2001, Funderud et al, 2012, Abeles and Gomez-Ramirez, 2014, Störmer et al, 2016, Schneider and Maguire, 2018).…”
Section: Introductionsupporting
confidence: 83%
“…Consistent with the predictions, the presence of non-zero OM has been previously directly confirmed (Nikulin et al, 2007, Nikulin et al, 2010) and the generation of evoked responses has been found to be consistent with the idea of BSM (Mazaheri and Jensen, 2008, Iemi et al, 2019, Iemi et al, 2021). Moreover, many empirical studies assessed cognitive functioning with simultaneous analysis of evoked responses and oscillations, with the results showing consistent correlation of evoked response amplitude and/or latency with the modulation in oscillations (Yordanova et al, 2001, Funderud et al, 2012, Abeles and Gomez-Ramirez, 2014, Störmer et al, 2016, Schneider and Maguire, 2018).…”
Section: Introductionsupporting
confidence: 83%
“…In addition to alpha pacemaker cells originally shown in the animal thalamus ( da Silva et al, 1973 ), widespread alpha activity suggests generators to be further located in early visual ( Bollimunta et al, 2008 ) and even higher-order cortical areas ( Florez et al, 2015 ; Haegens et al, 2015 ). Excitatory input to the visual cortex is regulated by functional inhibition in a feed-forward mechanism based on alpha oscillations, effectively controlling the excitability of the neural system per se ( Iemi et al, 2021 ; Jensen and Mazaheri, 2010 ). The inverse relationship between alpha power and excitability is corroborated by cross-modal evidence that strong ongoing alpha oscillations entail reduced single-unit firing rates in humans ( Chapeton et al, 2019 ) and primates ( Dougherty et al, 2017 ; Lundqvist et al, 2020 ), population-level activity such as local field potentials ( Potes et al, 2014 ; Spaak et al, 2012 ), and hemodynamic BOLD activity ( Becker et al, 2011 ; Goldman et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…In perceptual tasks, a transient state of lowered excitability inevitably affects behavior, as evident from longer reaction times ( Kelly and O’Connell, 2013 ; Zhang et al, 2008 ), lower confidence reports ( Samaha et al, 2017 ; Samaha et al, 2020b ), and lower detection rates of near-threshold stimuli ( Chaumon and Busch, 2014 ; Iemi and Busch, 2018 ). Accordingly, one recent study proposed that the alpha rhythm shapes the strength of neural stimulus representations by modulating excitability ( Iemi et al, 2021 ). Previous work by Michalareas et al, 2016 as well as our own data (see Supplementary Material) point toward an interaction between alpha and beta bands, as beta oscillations have very recently been implicated in mediating top-down signals from the frontal eye field (FEF) that modulate excitability in the visual cortex during spatial attention ( Veniero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, it is still a matter of debate by which mechanistic pathway, and at which processing stage the modulation of alpha power will impact behaviour. While it is (often implicitly) assumed that alpha oscillations impact behaviour via a modulation of neural excitability and thus early sensory processing, there is little evidence that shows a direct influence of alpha oscillation on changes in neural excitability and on subsequent behaviour 31,71 .…”
Section: Discussionmentioning
confidence: 99%